Economic Integration and Stock Market Comovement: An Empirical Study Pairing Pakistan’s Stock Exchange with 21 other Markets - Gohar, Raheel; Shah, Syed Zulfiqar Ali; Ahmad, Habib (Journal of Reviews on Global Economics, 2018)
Using daily stock returns from 2004 to 2014 for 21 countries paired with Pakistan, and using the Geweke methodology, the paper investigates the degree to which these stock markets are integrated with the Pakistani stock market. The paper also explores the factors that have an effect on the level of economic integration by applying fixed effect model. The result demonstrates statistically significant and high percentage of contemporaneous association between the 21 economies of the world and Pakistan. Greater comovement was observed between the equity markets during the period when Pakistani capital market and economy experience performance but less comovement was noted when Pakistan Stock Markets were under crises.